Multi-coating composite diaphragm for alkaline electrolytic cell, preparation method of multi-coating composite diaphragm and alkaline water electrolysis hydrogen production device

By adopting a multi-coated composite separator design in an alkaline electrolytic cell, including base film, inorganic ceramic layer, inorganic solid electrolyte layer and organic polymer layer, the problems of high energy consumption and low efficiency of traditional separators during electrolysis are solved, and the problems of high energy consumption and low efficiency in the electrolysis process are improved. The hydrogen purity and electrolytic efficiency are achieved, and more efficient hydrogen production by electrolyzing water is achieved.

CN119265631APending Publication Date: 2025-01-07HUADIAN CAOFEIDIAN HEAVY IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411412531.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional alkaline electrolytic cell separators have problems of high energy consumption, low efficiency and low hydrogen purity during the electrolysis process, and cannot meet the needs of high efficiency, low energy consumption and high purity.

Method used

The multi-coated composite separator design is adopted, including a base film, an inorganic ceramic layer, an inorganic solid electrolyte layer and an organic polymer layer, and the system performance is improved through directional coating, and the electrolytic efficiency and gas separation performance are optimized.

Benefits of technology

It significantly reduces the electrolytic voltage, improves the electrolytic efficiency and hydrogen purity, reduces energy consumption, and solves the problems of low electrolytic efficiency, high energy consumption and insufficient hydrogen purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078410040000091
    Figure BDA0005078410040000091
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogen production through water electrolysis, and discloses a multi-coating composite diaphragm for an alkaline electrolytic bath. The inorganic ceramic layer is arranged on one side of the base film; the inorganic solid electrolyte layer is arranged on the inorganic ceramic layer; and the polymer layer is arranged on the inorganic solid electrolyte layer. One side of the substrate layer is directionally coated with the inorganic ceramic layer, the inorganic solid electrolyte layer and the organic polymer layer, so that the performance of a cathode interface is improved, efficient transmission of hydroxyl ions to an anode is promoted, the speed and efficiency of the electrolysis process are remarkably improved, energy consumption is reduced, and the hydrogen production purity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and relates to a multi-coating composite diaphragm for an alkaline electrolytic cell, a preparation method thereof, and an alkaline water electrolysis hydrogen production device. Background Art

[0002] With the rapid development of wind and solar energy and other renewable energy in Northwest my country, a large amount of wind and solar energy has been developed and utilized. However, due to the low electricity consumption in Northwest China and the difficulty of grid output, the abundant wind and solar renewable electricity cannot be effectively transmitted to high-demand areas. In order to make full use of this renewable electricity and avoid resource waste, an effective strategy is to convert this electricity into hydrogen energy through water electrolysis.

[0003] Alkaline water electrolysis technology is currently the most mature technical route for hydrogen production by water electrolysis. In alkaline electrolyzers, the role of diaphragms is crucial. In addition to having good gas barrier properties to prevent hydrogen and oxygen from diffusing with each other, it must also allow the penetration of hydroxide ions and water, as well as excellent conductivity and corrosion resistance. However, traditional alkaline electrolyzer diaphragms show problems such as high energy consumption, low efficiency, and low hydrogen production purity during the electrolysis process, and cannot meet the urgent needs for high efficiency, low energy consumption, and high purity. For example, polyphenylene sulfide PPS has strong hardness, high corrosion resistance, and high glass transition temperature, and is widely used in diaphragms, but its shortcomings such as poor gas barrier properties, high resistance, and high energy consumption seriously restrict the development of hydrogen production by water electrolysis. Therefore, with the increasing demand for high efficiency, low energy consumption, and high hydrogen production purity, it is particularly important to develop a new high-efficiency, low-energy consumption multilayer composite diaphragm. Summary of the invention

[0004] In view of the above-mentioned technical problems, the present invention provides a multi-coated composite diaphragm for an alkaline electrolyzer, a preparation method and an alkaline water electrolysis hydrogen production device, wherein an inorganic ceramic layer, an inorganic solid electrolyte layer and an organic polymer layer are directionally coated on one side of the base layer, thereby improving the overall performance of the system, solving the industry pain points of low electrolysis efficiency, high energy consumption and insufficient hydrogen purity, and having important value in the field of alkaline water electrolysis hydrogen production.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a multi-coated composite diaphragm for an alkaline electrolytic cell, comprising:

[0007] Basement membrane;

[0008] An inorganic ceramic layer disposed on one side of the base film;

[0009] An inorganic solid electrolyte layer disposed on the inorganic ceramic layer;

[0010] A polymer layer is disposed on the inorganic solid electrolyte layer.

[0011] In one technical solution, the thickness of the inorganic ceramic layer is 8 to 30 μm.

[0012] In one technical solution, the thickness of the inorganic solid electrolyte layer is 5 to 15 μm.

[0013] In one technical solution, the thickness of the polymer layer is 3-10 μm.

[0014] In one technical solution, the base membrane is a polyphenylene sulfide porous membrane or a polytetrafluoroethylene porous membrane.

[0015] In one technical solution, the oxide in the inorganic ceramic layer is selected from one of aluminum oxide, titanium dioxide, zirconium oxide or silicon oxide.

[0016] In one technical solution, the solid electrolyte in the inorganic solid electrolyte layer is selected from lithium aluminum titanium phosphate Li 1+ x Al x Ti 2-x (PO4)3、Lithium Aluminum Germanium Phosphate Li 1+y Al y Ge 2-y (PO4)3, Lithium lanthanum titanium oxide Li z La 2 / 3-z / 3 TiO3, Lithium Lanthanum Zirconium Oxide Li7La3Zr2O 12 , Li 10 GeP2S 12 , Li 10 SnP2S 12 One of the following, where 0<x≤1, 0<y≤1, 0<z≤1.5.

[0017] In one technical solution, the polymer in the polymer layer is selected from polyphenylene sulfide, polyvinylidene fluoride, polyether sulfone, polysulfone, polycarbonate, polyimide or polytetrafluoroethylene.

[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned multi-coated composite diaphragm for an alkaline electrolytic cell, comprising the following steps:

[0019] 1) The inorganic ceramic mixed slurry is evenly coated on one side of the base film, dried at 70-90° C. for 40 min, and cured to form an inorganic ceramic layer;

[0020] 2) uniformly coating the inorganic solid electrolyte mixed slurry on the inorganic ceramic layer, drying at 90-120° C. for 30 min, and curing to form an inorganic solid electrolyte layer;

[0021] 3) The polymer mixed slurry is evenly coated on the inorganic solid electrolyte layer, and dried at 110-140° C. for 20 minutes to form an outermost polymer protective layer.

[0022] It is worth noting that the coating method includes but is not limited to dip coating, gravure printing, spray coating, extrusion coating, electrospinning and transfer coating.

[0023] In a third aspect, the present invention provides an alkaline water electrolysis hydrogen production device, comprising: a cathode; an alkaline electrolytic cell; the above-mentioned multi-coated composite diaphragm for the alkaline electrolytic cell; an electrolyte; and an anode.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention directional-coates an inorganic ceramic layer, an inorganic solid electrolyte layer and an organic polymer layer on one side of the substrate layer (the coating side faces the cathode when in use), improves the performance of the cathode interface, promotes the efficient transmission of hydroxide ions (OH-) to the anode, and significantly enhances the rate and efficiency of the electrolysis process. Compared with the non-directional or non-specific alkaline electrolytic cell design in the prior art, the design optimizes the electrochemical reaction kinetics, reduces energy consumption, and improves the overall performance of the system.

[0026] The present invention achieves a high degree of synergy between the coatings by controlling the coating thickness and annealing temperature during coating preparation, which not only enhances the overall mechanical strength and durability of the diaphragm, but also greatly improves the ion selective permeability. This effectively avoids the mutual penetration of hydrogen and oxygen, ensures the high efficiency of gas separation, and solves the safety hazard of excessive oxygen concentration in hydrogen.

[0027] Compared with the prior art, the water electrolysis device of the present invention reduces the electrolysis voltage by 10-20%, increases the electrolysis efficiency by 5-10%, reduces the energy consumption by 15-25%, and increases the purity of hydrogen production by 3-8%. These remarkable improvements are attributed to the improvement of the interface transmission efficiency by the directional coating design and the optimization of the overall performance by the multi-layer structure. It solves the industry pain points of low electrolysis efficiency, high energy consumption and insufficient hydrogen purity, and has important value in the field of hydrogen production by alkaline water electrolysis. DETAILED DESCRIPTION

[0028] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.

[0029] In the following examples, the base membrane is a polyphenylene sulfide (PPS) porous membrane with a porosity of 30%; a polytetrafluoroethylene (PTFE) porous membrane with a porosity of 40%. The purity of the alumina powder is ≥99.5%. Lithium lanthanum zirconium oxide Li7La3Zr2O12 The purity of the powder is ≥99%. The coating tool adopts a precision coating machine, model: CCT-1200.

[0030] Example 1

[0031] The preparation method of the three-layer composite diaphragm with PPS porous membrane as the base membrane in this embodiment is as follows:

[0032] 1) Base film pretreatment: The PPS porous membrane (length × width × height = 1000 mm × 500 mm × 50 μm) was washed with deionized water and dried naturally;

[0033] 2) Preparation of inorganic ceramic layer: 30 g of alumina powder, 100 ml of ethanol, 5 g of binder polyvinyl alcohol and 0.5 g of dispersant sodium hexametaphosphate were mixed and ultrasonically dispersed for 30 min to obtain an inorganic ceramic mixed slurry; the inorganic ceramic mixed slurry was evenly coated on one side of the PPS base film using a coating machine with a thickness controlled at 15 μm, and then placed in a constant temperature oven at 80° C. for 40 min to completely cure the inorganic ceramic mixed slurry to form an inorganic ceramic layer;

[0034] 3) Preparation of inorganic solid electrolyte layer: 20g lithium lanthanum zirconium oxide Li7La3Zr2O 12 The powder, 50 ml of ethanol, 30 ml of acetone, and 10 g of a binder polyvinylidene fluoride (PVDF) are mixed to obtain an inorganic solid electrolyte mixed slurry; the inorganic solid electrolyte mixed slurry is coated on the surface of the inorganic ceramic layer using a coating machine, the thickness of which is controlled to be 10 μm, and the mixture is placed in a constant temperature oven at 100° C. for 30 minutes to solidify and form an inorganic solid electrolyte layer;

[0035] 4) Preparation of polymer layer: 15 g of polyvinylidene fluoride (PVDF) powder and 100 ml of N-methylpyrrolidone (NMP) solvent were mixed to obtain a polymer mixed slurry; the polymer mixed slurry was coated on the inorganic solid electrolyte layer using a coater with a thickness of 5 μm, and placed in a constant temperature oven at 120° C. for 20 min to form an outermost polymer layer.

[0036] Example 2

[0037] The preparation method of the three-layer composite diaphragm with PPS porous membrane as the base membrane in this embodiment is as follows:

[0038] 1) Base film pretreatment: The PPS porous membrane (length × width × height = 1000 mm × 500 mm × 50 μm) was washed with deionized water and dried naturally;

[0039] 2) Preparation of inorganic ceramic layer: 30 g of alumina powder, 100 ml of ethanol, 5 g of binder polyvinyl alcohol and 0.5 g of dispersant sodium hexametaphosphate were mixed and ultrasonically dispersed for 30 min to obtain an inorganic ceramic mixed slurry; the inorganic ceramic mixed slurry was evenly coated on one side of the PPS base film using a coating machine with a thickness controlled at 15 μm, and then placed in a constant temperature oven at 70° C. for 40 min to completely solidify the inorganic ceramic mixed slurry to form an inorganic ceramic layer;

[0040] 3) Preparation of inorganic solid electrolyte layer: 20g lithium lanthanum zirconium oxide Li7La3Zr2O 12 The powder, 50 ml of ethanol, 30 ml of acetone, and 10 g of a binder polyvinylidene fluoride (PVDF) are mixed to obtain an inorganic solid electrolyte mixed slurry; the inorganic solid electrolyte mixed slurry is coated on the surface of the inorganic ceramic layer using a coating machine, the thickness of which is controlled to be 10 μm, and the mixture is placed in a constant temperature oven at 90° C. for 30 minutes to solidify and form an inorganic solid electrolyte layer;

[0041] 4) Preparation of polymer layer: 20 g of polyvinylidene fluoride (PVDF) powder and 100 ml of N-methylpyrrolidone (NMP) solvent were mixed to obtain a polymer mixed slurry; the polymer mixed slurry was coated on the inorganic solid electrolyte layer using a coater with a thickness of 5 μm, and placed in a constant temperature oven at 110° C. for 20 min to form an outermost polymer layer.

[0042] Example 3

[0043] The preparation method of the three-layer composite diaphragm with PPS porous membrane as the base membrane in this embodiment is as follows:

[0044] 1) Base film pretreatment: The PPS porous membrane (length × width × height = 1000 mm × 500 mm × 50 μm) was washed with deionized water and dried naturally;

[0045] 2) Preparation of inorganic ceramic layer: 30 g of alumina powder, 100 ml of ethanol, 5 g of binder polyvinyl alcohol and 0.5 g of dispersant sodium hexametaphosphate were mixed and ultrasonically dispersed for 30 min to obtain an inorganic ceramic mixed slurry; the inorganic ceramic mixed slurry was evenly coated on one side of the PPS base film using a coating machine with a thickness controlled at 20 μm, and then placed in a constant temperature oven at 80° C. for 40 min to completely cure the inorganic ceramic mixed slurry to form an inorganic ceramic layer;

[0046] 3) Preparation of inorganic solid electrolyte layer: 20g lithium lanthanum zirconium oxide Li7La3Zr2O 12The powder, 50 ml of ethanol, 30 ml of acetone, and 10 g of a binder polyvinylidene fluoride (PVDF) are mixed to obtain an inorganic solid electrolyte mixed slurry; the inorganic solid electrolyte mixed slurry is coated on the surface of the inorganic ceramic layer using a coating machine, the thickness of which is controlled to be 12 μm, and the mixture is placed in a constant temperature oven at 100° C. for 30 minutes to solidify and form an inorganic solid electrolyte layer;

[0047] 4) Preparation of polymer layer: 20 g of polyvinylidene fluoride (PVDF) powder and 100 ml of N-methylpyrrolidone (NMP) solvent were mixed to obtain a polymer mixed slurry; the polymer mixed slurry was coated on the inorganic solid electrolyte layer using a coater with a thickness of 7 μm, and placed in a constant temperature oven at 120° C. for 20 min to form an outermost polymer layer.

[0048] Example 4

[0049] The preparation method of the three-layer composite diaphragm with PPS porous membrane as the base membrane in this embodiment is as follows:

[0050] 1) Base film pretreatment: The PPS porous membrane (length × width × height = 1000 mm × 500 mm × 50 μm) was washed with deionized water and dried naturally;

[0051] 2) Preparation of inorganic ceramic layer: 25g of alumina powder, 100ml of ethanol, 4.17g of binder polyvinyl alcohol and 0.42g of dispersant sodium hexametaphosphate were mixed and ultrasonically dispersed for 30min to obtain an inorganic ceramic mixed slurry; the inorganic ceramic mixed slurry was evenly coated on one side of the PPS base film using a coating machine with a thickness controlled at 15μm, and then placed in a constant temperature oven at 80°C for 40min to completely cure the inorganic ceramic mixed slurry to form an inorganic ceramic layer;

[0052] 3) Preparation of inorganic solid electrolyte layer: 18g lithium lanthanum zirconium oxide Li7La3Zr2O 12 The powder, 50 ml of ethanol, 30 ml of acetone, and 9 g of a binder polyvinylidene fluoride (PVDF) are mixed to obtain an inorganic solid electrolyte mixed slurry; the inorganic solid electrolyte mixed slurry is coated on the surface of the inorganic ceramic layer using a coating machine, the thickness of which is controlled to be 10 μm, and the mixture is placed in a constant temperature oven at 100° C. for 30 minutes to solidify and form an inorganic solid electrolyte layer;

[0053] 4) Preparation of polymer layer: 12 g of polyvinylidene fluoride (PVDF) powder and 100 ml of N-methylpyrrolidone (NMP) solvent were mixed to obtain a polymer mixed slurry; the polymer mixed slurry was coated on the inorganic solid electrolyte layer using a coater with a thickness of 5 μm, and placed in a constant temperature oven at 120° C. for 20 min to form an outermost polymer layer.

[0054] Comparative Example 1

[0055] This comparative example is substantially the same as Example 1, except that no coating is applied on the PPS porous membrane.

[0056] Comparative Example 2

[0057] This comparative example is substantially the same as Example 1, except that an inorganic ceramic layer (coating thickness of 15 μm) is coated only on one side of the PPS porous membrane.

[0058] Comparative Example 3

[0059] This comparative example is basically the same as Example 1, except that an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic solid electrolyte layer (coating thickness is 10 μm) are sequentially coated on one side of the PPS porous membrane.

[0060] Comparative Example 4

[0061] This comparative example is basically the same as Example 1, except that an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic solid electrolyte layer (coating thickness is 10 μm) are coated on both sides of the PPS porous membrane respectively.

[0062] Comparative Example 5

[0063] This comparative example is basically the same as Example 1, except that an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic solid electrolyte layer (coating thickness is 10 μm) are sequentially coated on one side of the PPS porous membrane, and an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic ceramic layer (coating thickness is 10 μm) are sequentially coated on the other side.

[0064] Example 5

[0065] The preparation method of the three-layer composite diaphragm with PTFE porous membrane as the base membrane in this embodiment is as follows:

[0066] 1) Base membrane pretreatment: The PTFE porous membrane (length × width × height = 1000 mm × 500 mm × 50 μm) was washed with deionized water and dried naturally;

[0067] 2) Preparation of inorganic ceramic layer: 30 g of alumina powder, 100 ml of ethanol, 5 g of binder polyvinyl alcohol and 0.5 g of dispersant sodium hexametaphosphate were mixed and ultrasonically dispersed for 30 min to obtain an inorganic ceramic mixed slurry; the inorganic ceramic mixed slurry was evenly coated on one side of the PPS base film using a coating machine with a thickness controlled at 15 μm, and then placed in a constant temperature oven at 80° C. for 40 min to completely cure the inorganic ceramic mixed slurry to form an inorganic ceramic layer;

[0068] 3) Preparation of inorganic solid electrolyte layer: 20g lithium lanthanum zirconium oxide Li7La3Zr2O 12The powder, 50 ml of ethanol, 30 ml of acetone, and 10 g of a binder polyvinylidene fluoride (PVDF) are mixed to obtain an inorganic solid electrolyte mixed slurry; the inorganic solid electrolyte mixed slurry is coated on the surface of the inorganic ceramic layer using a coating machine, the thickness of which is controlled to be 10 μm, and the mixture is placed in a constant temperature oven at 100° C. for 30 minutes to solidify and form an inorganic solid electrolyte layer;

[0069] 4) Preparation of polymer layer: 15 g of polyvinylidene fluoride (PVDF) powder and 100 ml of N-methylpyrrolidone (NMP) solvent were mixed to obtain a polymer mixed slurry; the polymer mixed slurry was coated on the inorganic solid electrolyte layer using a coater with a thickness of 5 μm, and placed in a constant temperature oven at 120° C. for 20 min to form an outermost polymer layer.

[0070] Comparative Example 6

[0071] This comparative example is substantially the same as Example 1, except that no coating is applied on the PTFE porous membrane.

[0072] Comparative Example 7

[0073] This comparative example is substantially the same as Example 1, except that an inorganic ceramic layer (coating thickness of 15 μm) is coated only on one side of the PTFE porous membrane.

[0074] Comparative Example 8

[0075] This comparative example is basically the same as Example 1, except that an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic solid electrolyte layer (coating thickness is 10 μm) are sequentially coated on one side of the PTFE porous membrane.

[0076] Comparative Example 9

[0077] This comparative example is basically the same as Example 1, except that an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic solid electrolyte layer (coating thickness is 10 μm) are coated on both sides of the PTFE porous membrane respectively.

[0078] Comparative Example 10

[0079] This comparative example is basically the same as Example 1, except that: an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic solid electrolyte layer (coating thickness is 10 μm) are coated in sequence on one side of the PTFE porous membrane, and an inorganic ceramic layer (coating thickness is 15 μm) and an inorganic ceramic layer (coating thickness is 10 μm) are coated in sequence on the other side.

[0080] Performance test: The diaphragms prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were respectively installed in an alkaline electrolytic cell, and the electrolyte used was a 30% potassium hydroxide solution. The electrolysis conditions were: the working current density was set to 200 to 500 mA / cm 2 , the operating temperature was maintained at 80°C, the total circulation volume of the electrolyte was 5000ml, the pressure difference on both sides of the diaphragm was 0.1bar, and the electrolysis time was 24h. The electrolysis voltage and electrolysis efficiency, energy consumption, hydrogen production and purity at different current densities were statistically analyzed. The results are shown in Table 1.

[0081] Table 1 Performance test results

[0082]

[0083]

[0084] As can be seen from the table, compared with traditional diaphragms, single-layer composite diaphragms and double-layer composite diaphragms, the three-layer composite diaphragm shows lower electrolysis voltage (about 10-20% reduction) and higher electrolysis efficiency (about 5-10% increase) in the electrolysis performance test, which means that the multi-layer structure design helps to improve the overall performance of the electrolyzer; the three-layer composite diaphragm can effectively reduce the energy consumption in the electrolysis process (about 15-25% reduction), which is mainly due to the high ionic conductivity of the inorganic ceramic layer and the inorganic solid electrolyte layer, and the good corrosion resistance of the organic polymer layer. These characteristics work together to reduce energy loss; in addition, the purity of hydrogen produced by the three-layer composite diaphragm is significantly improved, which is because the multi-layer structure more effectively prevents gas cross-talk and impurity penetration.

[0085] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A multi-coated composite diaphragm for an alkaline electrolytic cell, characterized in that: include: Basement membrane; An inorganic ceramic layer disposed on one side of the base film; An inorganic solid electrolyte layer disposed on the inorganic ceramic layer; A polymer layer is disposed on the inorganic solid electrolyte layer.

2. The multi-coated composite diaphragm according to claim 1, characterized in that: The thickness of the inorganic ceramic layer is 8-30 μm.

3. The multi-coated composite diaphragm according to claim 1, characterized in that: The thickness of the inorganic solid electrolyte layer is 5-15 μm.

4. The multi-coated composite diaphragm according to claim 1, characterized in that: The thickness of the polymer layer is 3-10 μm.

5. The multi-coated composite diaphragm according to claim 1, characterized in that: The base film is a polyphenylene sulfide porous film or a polytetrafluoroethylene porous film.

6. The multi-coated composite diaphragm according to claim 1, characterized in that: The oxide in the inorganic ceramic layer is selected from one of aluminum oxide, titanium dioxide, zirconium oxide or silicon oxide.

7. The multi-coated composite diaphragm according to claim 1, characterized in that: The solid electrolyte in the inorganic solid electrolyte layer is selected from lithium aluminum titanium phosphate Li 1+x Al x Ti 2-x (PO4)3、Lithium germanium aluminum phosphate Li 1+y Al y Ge 2-y (PO4)3, Lithium lanthanum titanium oxide Li z La 2 / 3-z / 3 TiO3, Lithium Lanthanum Zirconium Oxide Li7La3Zr2O 12 , Li 10 GeP2S 12 , Li 10 SnP2S 12 One of the following, where 0<x≤1, 0<y≤1, 0<z≤1.

5.

8. The multi-coated composite diaphragm according to claim 1, characterized in that: The polymer in the polymer layer is selected from polyphenylene sulfide, polyvinylidene fluoride, polyether sulfone, polysulfone, polycarbonate, polyimide or polytetrafluoroethylene.

9. The method for preparing a multi-coated composite diaphragm for an alkaline electrolytic cell according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) The inorganic ceramic mixed slurry is evenly coated on one side of the base film, dried at 70-90°C for 40 min, and cured to form an inorganic ceramic layer; 2) uniformly coating the inorganic solid electrolyte mixed slurry on the inorganic ceramic layer, drying at 90-120°C for 30 min, and curing to form an inorganic solid electrolyte layer; 3) The polymer mixed slurry is evenly coated on the inorganic solid electrolyte layer and dried at 110-140°C for 20 min to form an outermost polymer protective layer.

10. An alkaline water electrolysis hydrogen production device, characterized in that: include: cathode; Alkaline electrolyzer; The multi-coated composite diaphragm for an alkaline electrolytic cell according to any one of claims 1 to 8; Electrolyte; anode.